A FRAMEWORK FOR EVALUATION OF PHARMACEUTICAL INDUSTRY DEVELOPMENT IN DEVELOPING COUNTRIES: EVIDENCE FROM IRAN - Shabaninejad, Hussein; Madani, Hesamoddin; Amineh, Zahra Ahani; Doostzadeh, Ebrahim (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: The pharmaceutical market is a complex market due to its complicated supply chain and the extent of government regulations in all aspects of the trade lifecycle of drug development. Considering the importance of pharmaceuticals for society and the relevant trend of globalization, managing pharmaceutical industry effectively and efficiently is vital, particularly in developing countries. The present study determines the factors affecting the development of the Iranian pharmaceutical industry based on pharmaceutical mangers’ point of view. Methods: In this study, we assessed managers’ perspective about the internal and external key factors affecting the development of pharmaceutical industry. Finally, their perspective about the solutions for the development of pharmaceutical industry was assessed. Accordingly, a self-designed questionnaire was sent to 65 managers at Tamin Pharmaceutical Investment Company, of which, 51 questionnaires were answered by the managers. Result: Most managers believed generic scheme reflect negatively on the development of the pharmaceutical industry and that external factors have a great impact on its improvement. They believe that branded generic transition along with supporting regulations, investment in Research and Development, and joint venture with foreign companies will improve the pharmaceutical industry. Conclusion: To sum up, for improving the pharmaceutical industry in the shortest time possible, improvement of technological capabilities and investment in R&D should be considered. Keywords: Pharmaceutical industry, Key factors, Generic scheme.